Method for preparing Ti2AlNb alloy with preferred orientation O phase
Through solid solution and constant stress treatment, the problem of random O phase distribution in Ti2AlNb alloy is solved, the optimal orientation of O phase and the target angle are achieved, and the mechanical properties and structure density of the alloy are improved.
Patent Information
- Application Number
- CN202411329956.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The O phase distribution in the existing Ti2AlNb alloy is random, without an optimal orientation, making it difficult to achieve precise control of the O phase and target angle.
Through solid solution treatment and constant stress treatment, the structure of the Ti2AlNb alloy is adjusted so that the O phase precipitated in the B2 matrix has an optimal orientation, and the angle between the two orientations is controlled to be 60°. Specific steps include heat treatment, wire cutting and constant stress treatment, and are processed using CNC wire cutting machine tools and Gleeble thermal simulation experimental machine.
The preferred orientation distribution of O phase in Ti2AlNb alloy is achieved, and the mechanical properties of the alloy are improved. The O phase is slat-shaped and has a more dense distribution, with a significant preferred orientation.
Smart Images

Figure CN119121092A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a TiAl intermetallic compound, in particular to a method for preparing a Ti2AlNb alloy with a preferred oriented O phase. Background Art
[0002] TiAl alloy has a series of advantages such as low density, high specific strength, high specific stiffness, good oxidation resistance, good high temperature creep performance, etc., and has broad application prospects in the field of aerospace. Ti2AlNb alloys with high Nb content have recently become a research hotspot. Among them, Ti2AlNb alloys with high Nb content have better room temperature plasticity, room temperature fracture toughness and better heat resistance than TiAl alloys with low Nb content. These excellent properties make Ti2AlNb-based alloys one of the most promising lightweight high temperature structural materials, and have broad application prospects in the fields of aviation and aerospace.
[0003] Ti2AlNb-based alloys are usually composed of B2, α2 and O phases. The O phase has an ordered orthorhombic crystal structure and is the main strengthening phase in Ti2AlNb-based alloys. The morphology of the O phase has a significant effect on the mechanical properties of the Ti2AlNb alloy. The O phase can be precipitated directly from the B2 matrix or α2 phase, or it can be generated by the percolation reaction between the α2 phase and the B2 matrix.
[0004] The organization and morphology of Ti2AlNb-based alloys are closely related to their mechanical properties. Using different preparation methods, as well as different hot working and heat treatment processes, the microstructure will change significantly, which will affect the performance of the alloy and thus affect the application of the alloy. After the Ti2AlNb alloy is treated under different processing conditions, the morphology of the O phase precipitated in the B2 matrix is needle-shaped, lath-shaped, equiaxed, etc. The precipitated O phase is randomly distributed on the B2 matrix without any preferred orientation, or the precipitation of the O phase in a very small local area has a preferred orientation.
[0005] Zheng Youping et al. heated Ti-22Al-25Nb alloy at 1100℃ for 10s -1 After being deformed at a rate of 50%, it was found that parallel O phase laths were observed in local areas of the organization after being kept at 900°C for 5 minutes. However, it did not realize how to accurately control the formation of O phase in Ti2AlNb alloy with preferential orientation, especially how to achieve a certain preferential orientation with a target angle between the two orientations, so as to accurately control the O phase in Ti2AlNb alloy. Summary of the invention
[0006] In view of the fact that although O phase can be generated in the existing Ti2AlNb alloy research, the precipitated O phase is randomly distributed without any preferential orientation, the inventors of the present invention are determined to make progress and design a method to achieve precise preferential orientation of the O phase precipitated in Ti2AlNb, so that the O phase precipitated in the obtained Ti2AlNb alloy has two orientations, and the angle between the two orientations is controlled to be 60°.
[0007] Specifically, the present invention achieves the above-mentioned invention objectives through the following technical solutions.
[0008] According to the present invention, there is provided a method for preparing a Ti2AlNb alloy in which the precipitated O phase has a preferred orientation, comprising the following steps: Step (1) heat treatment: performing a solution treatment on the Ti2AlNb alloy to adjust the structure of the Ti2AlNb alloy to contain α2 / O phase or α2 phase particles in the B2 matrix; Step (2) wire cutting: cutting a cylindrical compression specimen from the center of the Ti2AlNb alloy ingot by a CNC wire cutting machine; Step (3) constant stress treatment: the cut compression specimen is kept warm in the B2+O two-phase region of the Ti2AlNb alloy, and a constant stress is applied during the warming process for 30 minutes.
[0009] Preferably, in step (1), the solution treatment is carried out at 980°C-1060°C for 1-3 hours and then cooled. And further preferably, in step (1), the alloy is placed in a heat treatment furnace at 980°C for 1 hour and then taken out and water-cooled to room temperature.
[0010] Preferably, in step (3), the constant stress treatment is 780°C-860°C with a constant stress of 150MPa-550MPa for 30min. And further preferably, in step (3), the cut sample is subjected to a constant stress treatment on a Gleeble thermal simulation test machine, the sample temperature is raised to 780°C, a constant stress of 150MPa is applied, maintained for 30min, and then water-cooled to room temperature.
[0011] Preferably, the Ti2AlNb alloy contains 18-25% Al and 18-25% Nb by atomic percentage, with the balance being Ti and unavoidable impurities. And further preferably, the Ti2AlNb alloy contains 22% Al and 25% Nb by atomic percentage, with the balance being Ti and unavoidable impurities.
[0012] Preferably, the precipitated O phase has two orientations, and the angle between them is 60°.
[0013] In general, the present invention relates to a method for preparing a Ti2AlNb alloy, in particular a Ti2AlNb alloy with a specific composition of Ti-22Al-25Nb, in which the O phase has a preferred orientation. The alloy ingot sample is first subjected to a solid solution treatment at 980°C-1060°C for 1 hour and then water-cooled to room temperature, and then kept at 780°C-860°C for 30 minutes at a constant stress of 150MPa-550MPa and then water-cooled to room temperature. The structure of the obtained alloy after the solid solution treatment for 1 hour is B2+α2+O three-phase or B2+α2 two-phase. After the constant stress treatment, the structure of the alloy is B2+α2+O three-phase, lath-shaped O phases are precipitated in the alloy B2 matrix, and these O phases have two preferred orientations, and the angle between the two preferred orientations is 60°. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The above and other purposes, features and advantages of the present disclosure will become more apparent by describing the embodiments of the present disclosure in more detail in conjunction with the accompanying drawings. The accompanying drawings are used to provide a further understanding of the embodiments of the present disclosure and constitute a part of the specification. Together with the embodiments of the present disclosure, they are used to explain the present disclosure and do not constitute a limitation of the present disclosure. In the accompanying drawings, the same reference numerals generally represent the same parts, components or steps.
[0015] Figure 1 This is the scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Example 1 of the present invention after undergoing a heat treatment at 980°C / 1h + a constant pressure treatment at 780°C / 150MPa / 30min, wherein the white matrix is the B2 phase, the black particles are the α2 / O phase, and the gray phase is the O phase.
[0016] Figure 2 The scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Comparative Example 1 according to the present invention after being subjected to a heat treatment at 980°C / 1h+780°C / 30min.
[0017] Figure 3 This is the scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Example 2 of the present invention after being subjected to a 1060°C / 1h heat treatment + 820°C / 350MPa / 30min constant pressure treatment, wherein the white matrix is the B2 phase and the gray phase is the O phase.
[0018] Figure 4 The scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Comparative Example 2 according to the present invention after being subjected to a heat treatment at 1060°C / 1h+820°C / 30min.
[0019] Figure 5This is the scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Example 3 of the present invention after being subjected to a 1020°C / 1h heat treatment + a 780°C / 350MPa / 30min constant pressure treatment, wherein the white matrix is the B2 phase and the gray phase is the O phase.
[0020] Figure 6 The scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Comparative Example 3 according to the present invention after being subjected to a heat treatment at 1020°C / 1h+780°C / 30min.
[0021] Figure 7 This is the scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Example 4 of the present invention after being subjected to a 1060°C / 1h heat treatment + 860°C / 350MPa / 30min constant pressure treatment, wherein the white matrix is the B2 phase and the gray phase is the O phase.
[0022] Figure 8 The scanning electron microscope (BSE-SEM) microstructure of the Ti2AlNb alloy in Comparative Example 4 according to the present invention after being subjected to a heat treatment at 1060°C / 1h+860°C / 30min. DETAILED DESCRIPTION
[0023] Below, the exemplary embodiments according to the present disclosure will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are disclosed only as examples, rather than all embodiments of the present disclosure, and it should be understood that the present disclosure is not limited to the exemplary embodiments described herein.
[0024] In order to precipitate a large amount of O phase in subsequent treatment, the Ti2AlNb alloy is firstly subjected to solid solution treatment at 980℃-1060℃. After solid solution treatment, the alloy structure is a small amount of α2 / O phase or α2 phase particles distributed in the B2 matrix. After solid solution treatment, the alloy is cut into a size suitable for compression by wire cutting process. Then, it is treated at 780℃-860℃ with a constant stress of 150MPa-550MPa for 30min. After constant stress treatment, a large amount of O phase with preferred orientation is precipitated in the B2 matrix of the alloy.
[0025] The preparation method of the TiAl alloy used in the above experimental method is carried out according to the following steps: (1) Heat treatment: The Ti2AlNb alloy is first subjected to a solid solution treatment, and the alloy is adjusted to contain α2 / O phase or α2 phase particles in the B2 matrix through heat treatment; (2) Wire cutting: cutting a cylinder from the center of the above ingot by a CNC wire cutting machine; (3) Constant stress treatment: The cut compression specimens were kept warm in the B2+O two-phase region, and constant stress was applied during the warming process for 30 min.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. After the traditional solution aging treatment, the O phase precipitated in the Ti2AlNb alloy is randomly distributed without any preferred orientation. The O phase precipitated in the B2 matrix of the Ti2AlNb alloy in the present invention is regularly arranged and has a preferred orientation. The O phase has two orientations, and the angle between the two O phases with different orientations is 60°; 2. Compared with the traditional solution aging treatment, the O phase precipitated in the alloy of the present invention is in the form of laths, and the O phase distribution is more dense.
[0027] The present invention is further described below in conjunction with examples of characterization of material properties, but the present invention is not limited to the following examples. Embodiment 1
[0028] This embodiment is a method for preparing a Ti2AlNb alloy with a preferentially oriented O phase. The atomic percentage of the Ti2AlNb alloy used in the experiment is: Ti-22Al-25Nb, and the remainder is Ti and unavoidable impurities.
[0029] The preparation of the Ti2AlNb alloy having a preferentially oriented O phase is achieved by the following steps: (1) Heat treatment: Place the alloy in a heat treatment furnace at 980°C for 1 hour and then take it out and cool it to room temperature with water; (2) Wire cutting: Cut the sample from the center of the alloy after heat treatment in step 1 by using a CNC wire cutting machine. The sample is a cylinder with a size of Φ5*10mm; (3) Constant stress treatment: The cut specimens were subjected to constant stress treatment on a Gleeble thermal simulation test machine. The specimen temperature was raised to 780°C, a constant stress of 150 MPa was applied, and maintained for 30 min, and then water-cooled to room temperature. (4) Microstructure observation: The sample after constant stress treatment was cut parallel to the direction of applied stress, and the sample was mechanically polished until the surface was mirror-like and free of scratches. The microstructure was observed using a scanning electron microscope.
[0030] like Figure 1 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. A large number of lath-shaped O phases are precipitated in the B2 matrix of the alloy. These precipitated O phases have preferred orientations, mainly two orientations, and the angle between the O phases with different orientations is 60°.
[0031] The inventor Figure 1The volume area content of each phase is statistically as follows: B2 phase 25.74%, O phase lath 69.12%, α2 / O phase particles 5.14%.
[0032] Comparative Example 1 The alloy composition, treatment method, specific processing steps and observation method used in Comparative Example 1 are similar to those of Example 1. The only difference is that in the constant pressure treatment in step (3) of Example 1, in Comparative Example 1, only heat treatment is performed on the cut sample on a Gleeble thermal simulation test machine, that is, the sample temperature is raised to 780°C, maintained for 30 minutes, and then water-cooled to room temperature, without applying a constant stress of 150 MPa.
[0033] In comparative example 1, microstructure observation was performed as follows Figure 2 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. Basically, no lath-shaped O phase is precipitated in the B2 matrix of the alloy. Although the O phase is precipitated, the precipitated O phase does not have a preferred orientation.
[0034] The inventor Figure 2 The volume area content of each phase is statistically as follows: B2 phase 33.41%, O phase 60.42%, α2 / O phase particles 6.17%.
[0035] By comparing Comparative Example 1 with Example 1, it can be seen that an O-phase lath structure with a significant preferred orientation is obtained by the method of the present invention. Embodiment 2
[0036] This embodiment is a method for preparing a Ti2AlNb alloy with a preferentially oriented O phase. The atomic percentage of the Ti2AlNb alloy used in the experiment is: Ti-22Al-25Nb, and the remainder is Ti and unavoidable impurities.
[0037] The preparation of the Ti2AlNb alloy is achieved by the following steps: (1) Heat treatment: Place the alloy in a heat treatment furnace at 1060°C for 1 hour and then take it out and cool it to room temperature with water; (2) Wire cutting: Cut the sample from the center of the alloy after heat treatment in step 1 by using a CNC wire cutting machine. The sample is a cylinder with a size of Φ5*10mm; (3) Constant stress treatment: The cut specimens were subjected to constant stress treatment on a Gleeble thermal simulation test machine. The specimen temperature was raised to 820°C, and a constant stress of 350 MPa was applied for 30 min. The specimens were then cooled to room temperature with water. (4) Microstructure observation: The sample after constant stress treatment was cut parallel to the direction of applied stress, and the sample was mechanically polished until the surface was mirror-like and free of scratches. The microstructure was observed using a scanning electron microscope.
[0038] like Figure 3 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. A large number of lath-shaped O phases are precipitated in the B2 matrix of the alloy. These precipitated O phases have preferred orientations, mainly two orientations, and the angle between the O phases with different orientations is 60°.
[0039] The inventor Figure 3 The volume area content of each phase is statistically as follows: B2 phase 23.16%, O phase lath 76.84%.
[0040] Comparative Example 2 The alloy composition, treatment method, specific processing steps and observation method used in Comparative Example 2 are similar to those of Example 2. The only difference is that in the constant pressure treatment in step (3) of Example 2, in Comparative Example 2, only heat treatment is performed on the cut sample on a Gleeble thermal simulation test machine, that is, the sample temperature is raised to 820°C, maintained for 30 minutes, and then water-cooled to room temperature, without applying a constant stress of 350 MPa.
[0041] Microstructure observation was performed in Comparative Example 2. Figure 4 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. No lamellar O phase was observed to be precipitated in the B2 matrix of the alloy. Although the O phase was precipitated, the precipitated O phase was not observed to have a preferred orientation.
[0042] The inventor Figure 4 The volume area content of each phase is statistically as follows: B2 phase 27.08%; O phase 72.92%.
[0043] By comparing Comparative Example 2 with Example 2, it can be seen that an O-phase lath structure with a significant preferred orientation is obtained by the method of the present invention.
[0044] By comparing Examples 1 and 2, it can be seen that higher pressure and temperature treatment has a certain further promoting effect on the O-phase lath structure with preferred orientation. Embodiment 3
[0045] This embodiment is a method for preparing a Ti2AlNb alloy with a preferentially oriented O phase. The atomic percentage of the Ti2AlNb alloy used in the experiment is: Ti-22Al-25Nb, and the remainder is Ti and unavoidable impurities.
[0046] The preparation of the Ti2AlNb alloy is achieved by the following steps: (1) Heat treatment: Place the alloy in a heat treatment furnace at 1020°C for 1 hour and then take it out and cool it to room temperature with water; (2) Wire cutting: Cut the sample from the center of the alloy after heat treatment in step 1 by using a CNC wire cutting machine. The sample is a cylinder with a size of Φ5*10mm; (3) Constant stress treatment: The cut specimens were subjected to constant stress treatment on a Gleeble thermal simulation test machine. The specimen temperature was raised to 780°C, and a constant stress of 350 MPa was applied for 30 min. The specimens were then cooled to room temperature with water. (4) Microstructure observation: The sample after constant stress treatment was cut parallel to the direction of applied stress, and the sample was mechanically polished until the surface was mirror-like and free of scratches. The microstructure was observed using a scanning electron microscope.
[0047] like Figure 5 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. A large number of lath-shaped O phases are precipitated in the B2 matrix of the alloy. These precipitated O phases have preferred orientations, mainly two orientations, and the angle between the O phases with different orientations is 60°.
[0048] The inventor Figure 5 The volume area content of each phase is statistically as follows: B2 phase 18.01%, O phase lath 77.62%, α2 / O phase particles 4.37%.
[0049] Comparative Example 3 The alloy composition, treatment method, specific processing steps and observation method used in Comparative Example 3 are similar to those of Example 3. The only difference is that in the constant pressure treatment in step (3) of Example 3, in this Comparative Example 3, only heat treatment is performed on the cut sample on a Gleeble thermal simulation test machine, that is, the sample temperature is raised to 780°C, maintained for 30 minutes, and then water-cooled to room temperature, without applying a constant stress of 350 MPa.
[0050] In comparative example 3, microstructure observation was performed as follows Figure 6 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. No lamellar O phase was observed to be precipitated in the B2 matrix of the alloy. Although the O phase was precipitated, the precipitated O phase was not observed to have a preferred orientation.
[0051] The inventor Figure 6 The volume area content of each phase is statistically as follows: B2 phase 21.43%; O phase 72.12%; α2 / O phase particles 6.45%.
[0052] By comparing Comparative Example 3 with Example 3, it can be seen that an O-phase lath structure with a significant preferred orientation is obtained by the method of the present invention.
[0053] By comparing Examples 1 and 2 with this example, it can be seen that higher pressure and temperature treatment has a certain further promoting effect on the O-phase lath structure with preferred orientation. Embodiment 4
[0054] This embodiment is a method for preparing a Ti2AlNb alloy with a preferentially oriented O phase. The atomic percentage of the Ti2AlNb alloy used in the experiment is: Ti-22Al-25Nb, and the remainder is Ti and unavoidable impurities.
[0055] The preparation of the Ti2AlNb alloy is achieved by the following steps: (1) Heat treatment: Place the alloy in a heat treatment furnace at 1060°C for 1 hour and then take it out and cool it to room temperature with water; (2) Wire cutting: Cut the sample from the center of the alloy after heat treatment in step 1 by using a CNC wire cutting machine. The sample is a cylinder with a size of Φ5*10mm; (3) Constant stress treatment: The cut specimens were subjected to constant stress treatment on a Gleeble thermal simulation test machine. The specimen temperature was raised to 860°C, a constant stress of 350 MPa was applied, and maintained for 30 min. The specimens were then cooled to room temperature with water. (4) Microstructure observation: The sample after constant stress treatment was cut parallel to the direction of applied stress, and the sample was mechanically polished until the surface was mirror-like and free of scratches. The microstructure was observed using a scanning electron microscope.
[0056] like Figure 7 It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. A large number of lath-shaped O phases are precipitated in the B2 matrix of the alloy. These precipitated O phases have preferred orientations, mainly two orientations, and the angle between the O phases with different orientations is 60°.
[0057] The inventor Figure 7 The volume area content of each phase is statistically as follows: B2 phase 15.92%, O phase lath 84.08%.
[0058] Comparative Example 4 The alloy composition, treatment method, specific processing steps and observation method used in Comparative Example 4 are similar to those of Example 4. The only difference is that in the constant pressure treatment in step (3) of Example 4, in this Comparative Example 4, only heat treatment is performed on the cut sample on the Gleeble thermal simulation test machine, that is, the sample temperature is raised to 860°C, maintained for 30 minutes, and then water-cooled to room temperature, and a constant stress of 350 MPa is not applied.
[0059] In Comparative Example 4, microstructure observation was performed as follows Figure 8It can be seen that the microstructure of the Ti2AlNb alloy after constant stress treatment is composed of B2, α2 and O phases. No lamellar O phase was observed to be precipitated in the B2 matrix of the alloy. Although the O phase was precipitated, the precipitated O phase was not observed to have a preferred orientation.
[0060] The inventor Figure 8 The volume area content of each phase is statistically as follows: B2 phase 31.26%; O phase 68.74%.
[0061] By comparing Comparative Example 4 with Example 4, it can be seen that an O-phase lath structure with a significant preferred orientation is obtained by the method of the present invention.
[0062] At the same time, by comparing the results of the above groups of embodiments with the results of this embodiment, it can be seen that higher pressure and temperature treatment has a certain further promoting effect on the O-phase lath structure with preferred orientation.
[0063] In summary, the present invention obtains a Ti2AlNb alloy having a target orientation and orientation angle by heat treatment and constant pressure treatment on a Ti2AlNb alloy having an atomic percentage of Ti-22Al-25Nb, specifically: The solution treatment is carried out in the B2+α2+O three-phase region or the B2+α2 two-phase region. The sample after heat preservation is put into water for quenching, and the microstructure of the alloy is adjusted to a B2 matrix with α2 / O phase or α2 phase particles distributed in the B2 matrix. The O phase in the form of needles, laths, etc. cannot exist in the B2 matrix. The temperature of the constant stress treatment is in the B2+O two-phase region, and a higher temperature is conducive to the preferential orientation of the O phase.
[0064] The above exploration of the present invention found that the combination of heat treatment and constant pressure treatment of Ti2AlNb alloy is an effective way to obtain Ti2AlNb alloy with target orientation and orientation angle, which points out a clear way for further designing Ti2AlNb alloy according to actual mechanical properties requirements.
[0065] The basic principles of the present disclosure are described above in conjunction with specific embodiments. However, it should be noted that the advantages, strengths, effects, etc. mentioned in the present disclosure are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. are required by each embodiment of the present disclosure. In addition, the specific details disclosed above are only for the purpose of illustration and ease of understanding, and are not limitations. The above details do not limit the present disclosure to the necessity of adopting the above specific details to be implemented.
[0066] The block diagrams of the devices, apparatuses, equipment, and systems involved in this disclosure are only illustrative examples and are not intended to require or imply that they must be connected, arranged, and configured in the manner shown in the block diagrams. As will be appreciated by those skilled in the art, these devices, apparatuses, equipment, and systems can be connected, arranged, and configured in any manner. Words such as "including," "comprising," "having," and the like are open words, referring to "including but not limited to," and can be used interchangeably therewith. The words "or" and "and" used herein refer to the words "and / or," and can be used interchangeably therewith, unless the context clearly indicates otherwise. The word "such as" used herein refers to the phrase "such as but not limited to," and can be used interchangeably therewith.
[0067] It should also be noted that in the apparatus, device and method of the present disclosure, each component or each step can be decomposed and / or recombined. Such decomposition and / or recombination should be regarded as equivalent solutions of the present disclosure.
[0068] In this document, modifiers such as "first", "second", etc. without quantifiers are intended to distinguish different elements / components / circuits / modules / devices / steps, and are not used to emphasize the order, positional relationship, importance, priority, etc. In contrast, modifiers such as "first", "second", etc. with quantifiers can be used to emphasize the order, positional relationship, importance, priority, etc. of different elements / components / circuits / modules / devices / steps.
[0069] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use the present disclosure. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of the present disclosure. Therefore, the present disclosure is not intended to be limited to the aspects shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
[0070] The above description has been given for the purpose of illustration and description. In addition, this description is not intended to limit the embodiments of the present disclosure to the forms disclosed herein. Although multiple example aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, changes, additions and sub-combinations thereof.
Claims
1. A method for preparing a Ti2AlNb alloy in which the precipitated O phase has a preferred orientation, characterized in that: The steps include: Step (1) heat treatment: performing a solution treatment on the Ti2AlNb alloy to adjust the structure of the Ti2AlNb alloy to contain α2 / O phase or α2 phase particles in the B2 matrix; Step (2) wire cutting: cutting a cylindrical compression specimen from the center of the Ti2AlNb alloy ingot by a CNC wire cutting machine; Step (3) constant stress treatment: the cut compression specimen is kept warm in the B2+O two-phase region of the Ti2AlNb alloy, and a constant stress is applied during the warming process for 30 minutes.
2. The preparation method according to claim 1, characterized in that In the step (1), the solution treatment is carried out at 980°C-1060°C for 1-3 hours and then cooled.
3. The preparation method according to claim 2, characterized in that: The preparation method according to claim 1 is characterized in that in step (1), the alloy is placed in a heat treatment furnace at 980° C. and kept at that temperature for 1 hour, then taken out and water-cooled to room temperature.
4. The preparation method according to claim 1, characterized in that: In the step (3), the constant stress treatment is performed at 780°C-860°C and a constant stress of 150MPa-550MPa for 30 minutes.
5. The preparation method according to claim 4, characterized in that: In the step (3), the cut sample is subjected to a constant stress treatment on a Gleeble thermal simulation test machine, the sample temperature is raised to 780° C., a constant stress of 150 MPa is applied, maintained for 30 minutes, and then water-cooled to room temperature.
6. The preparation method according to claim 1, characterized in that: The Ti2AlNb alloy contains 18-25% Al and 18-25% Nb in atomic percentage, with the remainder being Ti and inevitable impurities.
7. The preparation method according to claim 6, characterized in that: The Ti2AlNb alloy contains 22% Al and 25% Nb in atomic percentage, with the remainder being Ti and unavoidable impurities.
8. The preparation method according to claim 1, characterized in that: The precipitated O phase has two orientations, and the angle between them is 60°.
Citation Information
Patent Citations
Structure refinement method for Ti2AlNb alloy through (O+B2) two-phase region aging treatment
CN106048486A
Method for regulating and controlling fine double-state or full lamellar structure of niobium-containing TiAl alloy
CN116219338A
High-thermal-strength Ti2AlNb alloy and thermal mechanical treatment method thereof
CN117403098A
Manufacturing method of 0-degree lamellar preferred orientation ultrahigh-plasticity high-niobium TiAl alloy
CN118291899A
O phase base ti-al-nb alloy and producing method therefor
JP2001152269A
